Understanding the transmission of monophasic Salmonella enterica 4,[5],12:i:- through alternate exposure methods in swine and demonstrating the importance of common biosecurity measures on swine farms - Harrison, Olivia Lynn (Kansas State University, 2021)
Salmonella is a major foodborne pathogen in the United States, causing approximately 31% of foodborne illnesses in the United States. Swine are capable of replicating Salmonella serotypes without showing clinical signs of infection and can produce contaminated pork products. The first experiment surveilled swine finishing operations to determine the distribution of Salmonella within farms and their environments, 186 samples from five finishing farms were collected in the fall of 2020. 100 (53%) of the samples were culture positive for Salmonella and 14 (7.5%) were confirmed Salmonella by PCR. Of the PCR positive samples, 12/14 were from either feces or locations in contact with feces such as the pen floor, gate, and fence. Salmonella was rarely observed in locations not typically associated with feces such as the feeders and waterers. 13/14 PCR positive samples originated from a single farm. These results suggest that Salmonella prevalence on surfaces and in feces is impacted by the farm and its current group of pigs, disease challenges, and the environment. The second experiment focused on Salmonella enterica 4,[5],12:i:- which is an emerging serotype commonly linked to contaminated pork products with a high degree of antimicrobial resistance. Transmission of this serotype to weaned pigs was conducted via contaminated feed, water, and aerosolized particles. S. enterica 4,[5],12:i:- was intermittently shed in the feces, rectal and nasal swabs, and in the environment of all inoculated pigs. Furthermore, S. enterica 4,[5],12:i:- was observed in the respiratory, lymphatic, and digestive systems of the infected pigs. Contaminated fomites such as feed and water are capable of S. enterica 4,[5],12:i- transmission and can introduce this serotype into the pork supply chain. The final experiment focused on the importance of biosecurity to prevent pathogen entry. Glo Germ is a fluorescent powder which can be used to track contamination in a simulated situation without risking the health of the farm. Glo Germ was spread prior to common biosecurity measures on a swine operation. Before and after photographs were used to evaluate whether Glo Germ had spread into the area following the biosecurity measure. Common biosecurity protocols are able to limit the spread of Glo Germ throughout a swine operation. Implementing similar visual techniques can help demonstrate to employees the importance of biosecurity on swine farms.
Keywords: Swine; Salmonella monophasic; Feed; Biosecurity